Cowardice : a Brief History. - Walsh, Chris (Princeton University Press, 2014)
Coward. It's a grave insult, likely to provoke anger, shame, even violence. But what exactly is cowardice? When terrorists are called cowards, does it mean the same as when the term is applied to soldiers? And what, if anything, does cowardice have to do with the rest of us? Bringing together sources from court-martial cases to literary and film classics such as Dante's Inferno, The Red Badge of Courage, and The Thin Red Line, Cowardice recounts the great harm that both cowards and the fear of seeming cowardly have done, and traces the idea of cowardice's power to its evolutionary roots. But.